(untitled) (Literatures of the World: Poetics, Mentality and Spirituality, 2016)
The article is dedicated to the analysis of the representation of Antillean landscape in the works by Édouard Glissant, Martinican writer who is considered as one of the most important figures of Francophone literature in the Caribbean basin. The object of the article is to expose the main ideas of the writer, his vision of the difficult formation of national consciousness in the Antilles and to analyze the landscape figures which illustrate specific traits of the author’s perception of the world and his philosophic views.